The effectiveness of salak pondoh peel ecoenzyme spray gel (Salacca edulis Reinw.) in pre-clinical evaluation of grade II burn healing - Kinasti Dwi Lestari; Aisyah Aulia Nugraha; Vibula Rosa Arumbina; Umu Kamilah; Rara Asti Azizah; Haris Setiawan; Oktira Roka Aji (Universitas Islam Negeri Sumatera Utara, 2025)
Burns are a serious health problem and require proper treatment for healing. Salak pondoh (Salacca edulis Reinw.) peel is known to contain high flavonoid compounds that have potential as antioxidants and antimicrobials. This study aims to determine the antibacterial activity of salak pondoh peel ecoenzyme and evaluate the effectiveness of its spray gel in healing burn wounds in rats. The research began with the preparation of eco-enzyme, flavonoid test using tube test and spectrophotometry, antibacterial test using disc diffusion method against Staphylococcus aureus and Pseudomonas aeruginosa, formulation and spray gel test, antioxidant test using DPPH method, and in vivo test to observe the percentage of second degree burn wound healing in male Wistar rats. The in vivo experiment involved 28 rats divided into five treatment groups: Control (K), Positive Control (KP), Negative Control (KN), 15% spray gel (P1), and 20% spray gel (P2). Data from in vitro and in vivo tests were analyzed using One-Way ANOVA (Analysis of Variance) with a significance level >0.05, followed by Tukey's Posthoc test. The results showed that 15% salak pondoh peel eco-enzyme showed strong antibacterial activity with an inhibition zone of 11.83 ± 0.76 against the growth of S. aureus and 10.83 ± 0.28 in the inhibition zone of P. aeruginosa. The 20% concentration (P2) showed the highest effectiveness in accelerating burn wound healing in test rats, with a healing rate of 99% (p < 0.05) on day 18. In conclusion, salak pondoh peel eco-enzyme showed antibacterial activity, and the eco-enzyme spray gel effectively accelerated burn wound healing.